해상 브이용 무선 통신체계 - 오진석; 전중성; Oh, Jin-Seok; Jeon, Joong-Sung (한국정보통신학회논문지, 2014)
Ocean buoys are operated for safe navigation and collecting ocean data. Recently, to reducing marine buoy's damage by ocean weather's bad condition and collision with vessels has been conducted in several field research. This paper's experiment is buoy condition monitoring about predefined data form by users. As a result using Wireless remote control board applying a radio signal processing algorithms, it can observe buoy's state at an interval of three minutes on the land. Acquired data type is changeable according to ocean weather condition or buoy's purpose of using in advance. Also, this paper conducted an experiment such as data-transmission's stability and wireless communication's availability. As results of the analysis of the transmitted data, the solar, wind and wave power indicates the maximum amount of power, 50 W, 20 W and 40 W respectively. The communication system proven through this research can apply to buoy or other ocean facility. 해상에 설치되는 브이는 선박의 안전항해 및 다양한 해양 데이터를 수집하기 위한 목적 등으로 운영되고 있다. 이러한 브이는 선박과의 충돌이나 해상 기상상태로 인한 브이의 피해가 자주 발생하면서 이러한 문제를 해결하기 위해 여러 분야에서 연구가 진행 중이다. 본 논문에서는 브이의 상태를 확인하기 위해 사용자가 사전에 정의한 데이터의 형식에 맞춰 브이의 상태를 모니터링 할 수 있게 실험을 하였다. 본 연구에서 설계한 무선 신호 처리 알고리즘을 적용한 무선 원격 제어 보드를 통하여 실험한 결과 육상에서 3분 간격으로 해상 브이에 상태를 모니터링 할 수 있다는 결과를 얻었다. 획득한 데이터의 종류는 브이가 적용되는 환경이나 목적에 따라 사전에 변경 할 수 있다. 이를 해상에 적용하기 위하여 데이터 전송 안정성을 실험하였고, 더불어 무선 통신망의 가용도에 영향을 미치는 것을 실험하였다. 전송된 데이터를 분석한 결과, 태양광, 풍력, 파력 발전에 대하여 각각 최대 50 W, 20 W, 40 W의 발전량을 보임을 확인할 수 있었다. 이러한 연구결과를 통하여 검증된 통신체계는 해상 브이뿐만 아니라 다른 해양구조물에도 적용 가능 할 것으로 예상된다.